« J’ai donné une âme à Winnetou » Interview avec l’acteur Pierre Brice sur le rôle de sa vie - Olivier Schwehm (Strenae)
This interview was used in the making of the documentary "Winnetou mustn't die,” broadcast by Arte on December 26, 2007. Pierre Brice, born Pierre Louis Le Bris, died on June 6, 2015, at the age of 86.